Impact of urban developments on the functional connectivity of forested habitats: a joint contribution of advanced urban models and landscape graphs. (March 2016) - Tannier, Cécile; Bourgeois, Marc; Houot, Hélène; Foltête, Jean-Christophe
Highlights: The relationship between urbanisation and ecological connectivity is analysed. Five prospective residential development scenarios are simulated. For each scenario, the volume of traffic on the road network is also simulated. Impacts on the functional connectivity of several ecological habitats are assessed. The decline in connectivity is more due to increased traffic than residential development. Abstract: The impacts of urban growth on biodiversity vary according to the form and the intensity of urbanisation. However, there is a lack of knowledge about the consequences of the type of urban structure (e.g. monocentric vs polycentric), the shape of urban boundaries, the local density of residential development, on the habitats of wildlife species. In this context, this paper focuses on the relationship between forms of urbanisation and functional connectivity of ecological habitats. In the urban region of Besançon (eastern France), three emblematic protected species were selected to represent forest mammals. From the initial state describing current land cover, five prospective residential development scenarios were simulated, corresponding to the form currently most commonly found (e.g. compact development, transit-oriented development, polycentric development). For each scenario, we also simulate the volume of traffic on the road network to allow for the barrier effect of roads on habitat connectivity. Then, for each development scenario, we model the functional connectivity of habitats of the various target species using landscape graphs. Results show that compact city maintains more functional connectivity for all the species considered whereas urban sprawl leads to much more marked impacts. Moderately compact and regulated periurban scenarios have intermediate levels of impact. The transit-oriented development scenario produces specific impact values according to the species. An interesting point is that the decline in functional connectivity of forest habitats is more due to increased traffic than residential development proper. This outlines the relevance of integrated models for simulating both land use and transport at a fine scale.